Proceedings of the 20th ACM International Conference on Multimedia 2012
DOI: 10.1145/2393347.2393399
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder

Abstract: Most artworks are explicitly created to evoke a strong emotional response. During the centuries there were several art movements which employed different techniques to achieve emotional expressions conveyed by artworks. Yet people were always consistently able to read the emotional messages even from the most abstract paintings. Can a machine learn what makes an artwork emotional? In this work, we consider a set of 500 abstract paintings from Museum of Modern and Contemporary Art of Trento and Rovereto (MART),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 29 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…However, this difference may well be explained by the different test stimuli used in the experiments (homogeneously colored squares vs. artworks). In another recent investigation, Yanulevskaya et al (2012) showed that bright and saturated colors generated positive emotions, while darker colors tended to evoke negative emotions. Moreover, Amirshahi et al (2013) described a strong correlation of beauty ratings with color quantization values and mean color value in a large dataset of figurative paintings.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, this difference may well be explained by the different test stimuli used in the experiments (homogeneously colored squares vs. artworks). In another recent investigation, Yanulevskaya et al (2012) showed that bright and saturated colors generated positive emotions, while darker colors tended to evoke negative emotions. Moreover, Amirshahi et al (2013) described a strong correlation of beauty ratings with color quantization values and mean color value in a large dataset of figurative paintings.…”
Section: Discussionmentioning
confidence: 95%
“…Nowadays, image analysis is based on firmly established empirical methods rather than on vague intuitive grounds. For example, computer-assisted algorithms are used to extract image features that characterize aesthetic images (Datta, 2006; Graham and Field, 2007; Redies et al, 2007a, 2012; Amirshahi et al, 2012), to predict emotional responses to paintings (e.g., Yanulevskaya et al, 2012) or to categorize painting styles (Wallraven et al, 2009). It is hoped that, in combination, the two approaches of experimental aesthetics will help us to understand what the specific properties of aesthetic images are and how they elicit brain responses that correlate with aesthetic judgments by the observers (Redies, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously shown that observers with no training in art awarded highly consistent ratings of valence and arousal to abstract works of art [ 39 , 40 ]. In addition, in a computational vision study, it was possible to train a classifier to correctly predict human emotion judgments for abstract artworks based on basic visual features [ 41 ]. These findings are in line with the idea that valence and arousal judgments are formed, at least in part, on the basis of visual features of the artworks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, efforts for visual analysis fall far behind. The closest that comes to sentiment analysis for visual content is the analysis of aesthetics [6,15,22], interestingness [12], and affect or emotions [13,21,37,36]. To this end, either low-level features are directly taken to predict emotion [18,13], or indirectly by facial expressions detection [32] or user intent [11].…”
Section: Related Workmentioning
confidence: 99%